Uncertainty of sound insulation measurement in laboratory - Wszołek, Tadeusz (Archives of Acoustics, 2007)
Protection against noise is one of the six essentials requirements of the European Uniondirective. In buildings airborne sound insulation is used to define the acoustic quality of wallsbetween rooms. However the evaluation of sound insulation /index/ is sometimes difficult oreven ambiguous, both in field and laboratory measurements, in spite of the fact that there aresome unified measurement procedures specified in the ISO 140 standards. There are problemswith the reproducibility and repeatability of the measurement results. Some difficultiesmay be caused by non-diffuse acoustic fields, non uniform reverberation time or errors of thereverberation time measurements. Some minor problems are also posed by flanking transmissionand the S/N ratio. The paper includes an analysis of partial uncertainties of the abovementioned measurement components and their influence on the combined uncertainty in 1/3octave frequency bands and the sound reduction index determined according to ISO 140-3,using the uncertainty propagation law. All of the analysis and calculations performed in thepaper concern the conjugated reverberation rooms and measurement set-up located in AGHUSTDepartment of Mechanics and Vibroacoustics in Kraków.